AI and Human Interaction in Translation Education: Perceptions of Indonesian EFL Lecturers - Dahlan, Suratman; Dollah, Syarifuddin; Weda, Sukardi; Sunra, La; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2025)
This study investigates Indonesian lecturers’ perceptions of Artificial Intelligence (AI) in translation education, focusing on how technology reshapes pedagogy, student engagement, and institutional practices. Employing a qualitative phenomenological design, data were collected through semi-structured interviews with lecturers who actively integrated AI tools into translation teaching. Thematic analysis identified five major findings: perceived benefits of AI for efficiency and accessibility, pedagogical shifts and curriculum integration, challenges of student dependence and diminished critical thinking, ethical and responsible use of AI tools, and AI as a catalyst for institutional and administrative efficiency. While lecturers acknowledged AI’s transformative potential in facilitating translation tasks, they also highlighted risks of overreliance, ethical dilemmas, and uneven access. The study concludes that integration requires balancing technological affordances with humanistic values, fostering critical AI literacy, and embedding ethical considerations in pedagogy. These findings contribute to ongoing debates on AI-enhanced translation pedagogy in global higher education institutions.